Nilai-Nilai Pendidikan Karakter Pada Anak Usia Dini Perspektif QS. Al-Baqarah Ayat 83 - Yanto, Murni (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
At this time, young children will be very sensitive in absorbing information and imitating what they see and feel, so the values ​​of character education and teaching them morals will be firmly embedded in their souls. Islam offers children an image or perspective for character education. The Koran, especially Q.S. Al-Baqarah verse 83, is a holy book that can be a source of inspiration for educators who work with children. From the point of view of Q.S. Surah Al-Baqarah verse 83, the aim of this research is to describe and analyze the importance of character education management in early childhood. This study was conducted in the library. Researchers use documentation methods when collecting data. The Ijmaly interpretation method is the method used by researchers. Researchers used qualitative data analysis to evaluate the data. From the point of view of Q.S. Al-Baqarah verse 83, research findings on the values ​​of managing character education in early childhood are religious values; prayer, monotheism, and the importance of responsibility; filial piety to parents and the importance of social services; do good to relatives, orphans, poor people and the poor; be kind to everyone and emphasize the importance of discipline; start praying. The Importance of Character Education Management from an Early Childhood Perspective Q.S. Al-Baqarah verse 83 is religious in character; taught to pray at the age of 5-7 years and recite the Koran at the age of 1-2 years. nature of accountability; Children between the ages of 4 and 5 begin to learn to be filial to their parents.